Strategi Peningkatan Kepatuhan Pembayaran PBB Melalui Pembentukan Satgas di Kecamatan Tandes: Strategi Peningkatan Kepatuhan Pembayaran PBB Melalui Pembentukan Satgas di Kecamatan Tandes - Laluna Nandita Hapsari; Niniek Imaningsih; Cholid Fadil (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The internship conducted at UPTB 4 of the Regional Revenue Agency (BAPENDA) in Surabaya from September 23 to December 31, 2024, aimed to increase revenue from Property Tax (PBB) through the implementation of data verification and validation methods, as well as the establishment of task forces. This activity also provided students with an opportunity to deepen their understanding of local tax management and strategies to raise public awareness about tax obligations.During the verification stage, taxpayer data, such as names, addresses, and Property Identification Numbers (NOP), was cross-checked to ensure the accuracy of the recorded information. This process was designed to facilitate the smooth distribution of documents, including Property Tax Notification Letters (SPPT), to taxpayers. Additionally, the formation of task forces conducting direct visits to taxpayers served as an effective means of reminding the public about their tax payment obligations and enhancing compliance rates.The results of this internship showed improvements in the efficiency of tax administration, although some challenges, such as data discrepancies and absentee taxpayers, remain to be addressed. Overall, the internship provided significant benefits, both for students in honing their practical skills and for the agency through the introduction of innovative ideas to refine the tax management system.